De gustibus, or How Philosophy and Aesthetics can Reflect on Food (Itinera, 2016)
This paper recreates some of the most relevant theoretical moments of the development of philosophical analysis of issues about food, nutrition, gastronomy and cuisine, in particular: (1) cognitive approach proposed by Carolyn Korsmeyer; (2) the reflection of Jèssica Jaques, who has been focusing on two aspects: what she called “Gustatory Philosophy” and “Aesthetics of Gastronomy”; (3) the main theses proposed by Nicola Perullo, who has introduced in Italy the aesthetics of food intended as a philosophical discipline.